1930
DOI: 10.1001/archpedi.1930.01930180036004
|View full text |Cite
|
Sign up to set email alerts
|

Human Milk Flow

Abstract: AND BETTY NIMS DETROIT Though many rational theories have been advanced on the subject, it is not known whether nervous, chemical or glandular agents operate to start the flow of milk. Even seemingly convincing experimental evidences are contradictory concerning the causes of the hypertrophy of the mammary glands during pregnancy and their secretory activity immediately after parturition. There is a general opinion that nervous shock, certain psychic states caused by the presence or absence of the suckling ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1931
1931
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…In a large study of 200 women who expressed milk manually for 24 h, the volume ranged from 0.8 to 1.8 liters for a mean daily loss of 400 mg calcium (582,584). Individual women were identified who had sustained production of up to 3 liters of milk per day during 6 -12 mo of lactation (419,583,838); analysis of their milk revealed daily calcium losses of 500-1,200 mg (419, 838). However, manual expression of milk can yield much greater volumes than a suckling baby demands, thereby overestimating milk production.…”
Section: Skeletal and Mineral Physiology During Lactation And Posmentioning
confidence: 99%
See 2 more Smart Citations
“…In a large study of 200 women who expressed milk manually for 24 h, the volume ranged from 0.8 to 1.8 liters for a mean daily loss of 400 mg calcium (582,584). Individual women were identified who had sustained production of up to 3 liters of milk per day during 6 -12 mo of lactation (419,583,838); analysis of their milk revealed daily calcium losses of 500-1,200 mg (419, 838). However, manual expression of milk can yield much greater volumes than a suckling baby demands, thereby overestimating milk production.…”
Section: Skeletal and Mineral Physiology During Lactation And Posmentioning
confidence: 99%
“…However, this should be mitigated by the infant consuming solid foods by 6 mo of age and a reduction in the amount of milk produced. On the other hand, a professional "wet nurse" can have high volumes of milk output that are sustained for long intervals (419,583,838), so ongoing bone loss seems inevitable. However, no bone density data have been reported for such women.…”
Section: Human Datamentioning
confidence: 99%
See 1 more Smart Citation
“…There is substantial evidence that infant demand is the major regulatory factor for volume of milk secreted during lactation. Studies of early investigators (4) indicate that wet nurses could secrete greater than 3,000 mL/d and mothers of twins and triplets are reported to secrete 2,000 to 3,000 mL/d by nursing about 12-15 times per day (5). Thus, the average quantity of milk secreted by lactating women for a normal single infant is far less than maternal capacity for milk production.…”
Section: The Regulation Of Human Milk Secretionmentioning
confidence: 99%
“…When mothers secrete a milk with a low energy density, increased suckling by their infants stimulates an increase in milk secretion. In the early studies of Macy et al [9], wet nurses were reported to secrete 13,000 g/day, and mothers who exclusively nurse twins or triplets can produce 2,000-3,000 g/day by nursing about 15 times/day [10]. Thus, the human potential for milk production is far greater than the average demand of a thriving single infant.…”
Section: Regulation Of Human Milk Productionmentioning
confidence: 99%